KORELASI ANTARA PENGUASAAN KOSAKATA DENGAN KETERAMPILAN MENULIS PUISI SISWA KELAS V C - Rizka Putri Salsadila; Siti Halidjah; Dyoty Auliya Vilda Ghasya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to determine the correlation between vocabulary mastery and poetry writing skills for grade V C elementary school students, Pontianak City. The research method used is descriptive correlational method. The population in this study were all fifth grade students of State Elementary School 03 Pontianak City. The sample used was 25 students of class V C State Elementary School 03 Pontianak City using purposive sampling technique. The data collection technique used is a test technique using multiple choice questions to measure students' vocabulary mastery and a test of students' poetry writing skills. The data analysis technique performed statistically with a significance level of 5% showed that there was a correlation between vocabulary mastery and poetry writing skills with r count 0.924 > r table 0.396. Because with r count > r table, it can be concluded that there is a correlation between vocabulary mastery and students' poetry writing skills.Keywords: Correlation, Vocabulary Mastery, Poetry Writing Skill